2019
DOI: 10.1016/j.ijnss.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ knowledge, willingness, and attitudes toward the first aid behavior as bystanders in traffic accident trauma: A cross-sectional survey

Abstract: Objectives The purpose of the study was to investigate the nursing students’ levels of the knowledge, willingness, and attitudes toward first aid behavior as bystanders in road traffic accident and the related factors. Methods A total of 475 nursing students were recruited by convenience choosing in Tianjin University of Traditional Chinese Medicine. The nursing students’ self-efficacy, core self-evaluation, knowledge, willingness and attitudes toward first aid behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 19 publications
2
19
1
6
Order By: Relevance
“…Such classification returns to us that Physical Education students have regular knowledge. This result is similar to that found in other studies (Ganfure et al, 2018;Halawani et al, 2019;Pei et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Such classification returns to us that Physical Education students have regular knowledge. This result is similar to that found in other studies (Ganfure et al, 2018;Halawani et al, 2019;Pei et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…People’s affect toward first aid was found to be correlated with their confidence in dealing with medical emergencies. A study by Pei et al revealed that nursing students’ willingness, knowledge, and attitudes toward first aid behavior were positively correlated with their self-efficacy of first aid [ 26 ]. Choi et al [ 27 ] found that students with higher self-efficacy were more willing to perform CPR.…”
Section: Introductionmentioning
confidence: 99%
“…Значительное количество случаев смерти из-за нарушения дыхания или кровотечений может быть тут же предотвращено силами обычных свидетелей аварии, если они имеют необходимые знания в области оказания первой помощи 1 [5,6].…”
unclassified
“…В Европе национальные общества Красного Креста и Красного Полумесяца только за 2014 год обучили навыкам оказания первой помощи 4 161 366 человек. Доля граждан, обученных приемам первой помощи, может достигать 95 % (для стран Западной Европы) 6 . В опросе, проведенном в Стокгольме в 2010 году по приемам первой помощи, показатель успешности составил 52 % [7].…”
unclassified
See 1 more Smart Citation